Leveraging On Information Technology To Teach Construction Law To Built Environment Students: A Knowledge-based System (KBS) Approach - Arain, Faisal Manzoor (Penerbit Universiti Sains Malaysia, 2009)
Construction law is a vital component of the body of knowledge that is needed by construction professionals in order to successfully operate in the commercial world of construction. Construction law plays an important role in shaping building projects. Construction projects are complex because they involve many human and non-human factors and variables. Teaching construction law is therefore a complex issue with several dimensions. In recent years, Information Technology (IT) has become strongly established as a supporting tool for many professions, including teachers. If faculty members have a knowledge base established on similar past projects, it would assist the faculty members to present case studies and contractually based scenarios to students. This paper proposes potential utilisation of a Knowledge-based System (KBS) for teaching construction law to built environment students. The KBS is primarily designed for building professionals to learn from similar past projects. The KBS is able to assist professionals by providing accurate and timely information for decision making and a user-friendly tool for analysing and selecting the suggested controls for variations in educational buildings. It is recommended that the wealth of knowledge available in the KBS can be very helpful in teaching construction law to built environment students. The system presents real case studies and scenarios to students to allow them to analyse and learn construction law. The KBS could be useful to students as a general research tool because the students could populate it with their own data and use it with the reported educational projects. With further generic modifications, the KBS will also be useful for built environment students to learn about project management of building projects; thus, it will raise the overall level of professional understanding, and eventually productivity, in the construction industry.